Off-Record Politeness Strategy in The Day After Tomorrow Film - Selya Nedjua Resti Yohana; Rosita Ambarwati; Theresia Budi Sucihati (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2025)
This study examined the use of off-record politeness strategies in the film The Day After Tomorrow, focusing on their role in crisis communication. The analysis was based on Leechs politeness principle to evaluate the level of politeness and on Brown and Levinsons theory to classify the strategies used. Eighteen utterances containing off-record strategies were identified and analyzed. Among the sub-strategies, presuppose was found to be the most frequently used, indicating that characters often relied on shared assumptions to communicate politely during high-pressure situations. The findings demonstrated that indirectness through off-record strategies served as a pragmatic tool to reduce the impact of face-threatening acts and maintain social harmony. This study concluded that politeness in crisis contexts is effectively conveyed through indirect speech, especially by using presuppositions. The results offer insights for further research on politeness in various communicative settings and potential applications in language education and discourse analysis.